Utilization of Quizizz Application in PAI Learning to Improve Student Understanding at SMP Swasta Tunas Karya Batang Kuis Class VIII - Muhammad Dandi Nugroho; Elva Savira (Jurnal Pendidikan Islam, 2025)
This study aims to analyze the effectiveness of using the Quizizz application in improving student understanding of Islamic Religious Education (PAI) subjects in class VIII SMP Swasta Tunas Karya Batang Kuis, Karo Regency. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation of student learning outcomes. The observed aspects include understanding of basic concepts, accuracy of answers, application of Islamic values, learning independence, consistency of understanding, speed of answering, self-reflection, and enthusiasm for learning. The results showed that the use of Quizizz significantly increased student engagement and learning motivation. Most students showed learning outcomes in the high to very high category. They were more enthusiastic, and active and showed a better understanding of the material compared to conventional learning methods. In addition, this application also makes it easier for teachers to evaluate and reflect on learning through the automatic report feature available. It can be concluded that Quizizz is an effective interactive learning media to improve the quality of PAI learning, and can create a fun and adaptive learning atmosphere to the needs of the digital generation.